Answer:
8.12
Step-by-step explanation:
We obtain the distance between x and y
d = sqrt[(x2 - x1)² + (y2 - y1)²]
d = sqrt[(1 - 2)² + (2 - 6)²]
d = sqrt[1 + 16)
d = sqrt(17)
d² = 17
From Pythagoras rule;
Hypotenus = sqrt(Adjacent² + opposite²)
Hence,
Hypotenus = sqrt(17 + 7²)
Hypotenus = sqrt(17+ 49)
Hypotenus = sqrt(66)
Hypotenus = 8.124
Hypotenus = 8.12
Answer:
n = 3
e = 5
Step-by-step explanation:
10n + 3e = 45
2n + 5e = 31
10n + 3e = 45
10n + 25e = 155
o + 22e = 110
e = 5
to fix 5 into the first equation
10n + 3(5) = 45
10n + 15 = 45
10n = 45 -15
10n = 30
n = 3
Answer:
c) 50 degrees
Step-by-step explanation:
360-260 = 100 degree central angle
inscribed angle = 1/2 (100) = 50
Answer:
2791
Step-by-step explanation:
Yea